Pengaruh Efikasi Diri, Aktivitas Belajar, Fasilitas Sekolah, Pendidikan Orang Tua dan Teman Sebaya Terhadap Prestasi Belajar Mata Pelajaran Ekonomi Siswa Kelas XI MAN 3 Kota Padang - Rusnida, Belina; Wahyuni, Sri; Eprillison, Vivina (Jurnal Horizon Pendidikan, 2022)
This study aims to analyze the influence of self-efficacy, learning activities, school facilities, education of parents and peers on the learning achievement of Economics subjects of Class XI MAN 3 Students in Padang City. The results of data analysis in this study found that there was an influence of variables of self-efficacy, learning activities, school facilities, the education of parents and peers together on the learning achievement of Economics subjects of class XI MAN 3 Students in Padang City. The results of each variable can be decomposed based on two levels as follows: First, students who do not participate in the detailed extracurricular, namely the probability value of the self-efficacy variable (0.0000), learning activities (0.0017), school facilities (0.0003), parental education (0.0044) and peers (0.0000) affect student learning achievement which can be proven by a probability value smaller than α (0.05). Second, students who take part in extracurricular that can be detailed, namely the probability value of self-efficacy variables (0.0000), learning activities (0.0256), school facilities (0.0041), parents' education (0.0259) and peers (0.0000) affect student learning achievement which can be proven by a probability value smaller than α (0.05).